BEBAN MAHKAMAH KONSTITUSI DALAM MEMUTUS PERSELISIHAN TENTANG HASIL PEMILIHAN UMUM SERENTAK 2024 - Muhammad Raihan (Universitas Negeri Islam Kediri, 2023)
The Simultaneous General Election System was first implemented in Indonesia in the 2019 General Election period and the simultaneous Regional Head Election (Pilkada) in 2020. As there are ongoing rumours about the upcoming simultaneous elections will again be held in 2024, at the same time there is a discourse on how the simultaneous elections will be implemented. The Constitutional Court recommends six implementation constitutional models of simultaneous elections in order to legally be elected by legislators and election administrators. Based on the selected Simultaneous Election model, it will be held on February 14, 2024 to elect members for DPR, DPD, both Provincial and City DPRD, President and Vice President, followed by the Regional Head Election which will be held in November 2024. Considering that the entire series of simultaneous General Election events will be held in the same year, the purpose of this research is to answer the questions regarding the chosen models in carrying out the 2024 Simultaneous General Election and the burden of the Constitutional Court in deciding disputes over both the general elections (PHPU) and the Regional Head Elections. This study uses a normative juridical research method, with a statutory approach and a conceptual approach. The result of this study indicates it is more ideal to separate the national election and local level elections. The 2024 simultaneous election model will increase the overburden of Constitutional Court in deciding election results disputes, such as time, incoming cases, and human resources who handle and decide the disputes.